2011
DOI: 10.1177/0194599811409837
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guideline: Polysomnography for Sleep‐Disordered Breathing Prior to Tonsillectomy in Children

Abstract: Objective. This guideline provides otolaryngologists with evidence-based recommendations for using polysomnography in assessing children, aged 2 to 18 years, with sleep-disordered breathing and are candidates for tonsillectomy, with or without adenoidectomy. Polysomnography is the electrographic recording of simultaneous physiologic variables during sleep and is currently considered the gold standard for objectively assessing sleep disorders.Purpose. There is no current consensus or guideline on when children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
378
2
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 394 publications
(392 citation statements)
references
References 105 publications
(156 reference statements)
2
378
2
10
Order By: Relevance
“…Practice guidelines from the American Academy of Sleep Medicine and American Academy of Pediatrics recommend PSG to confirm and characterize OSAS before adenotonsillectomy, 1,2,11 whereas the American Academy of Otolaryngology-Head and Neck Surgery recommends PSG for children with certain complex medical conditions or when there is discordance between tonsil size and reported severity of OSAS symptoms. 12 Less work has been done to define what adjunctive measures, in addition to PSG, may assist pediatricians, otolaryngologists, and families who are considering adenotonsillectomy to understand what adverse impact OSAS is having for the child and what the probability is that this adverse impact will be ameliorated by surgery. For example, few studies have examined whether baseline OSAS symptoms can predict postoperative changes in parentperceived behavior, sleepiness, and quality of life, outcomes that assume key importance to families, regardless of PSG results.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Practice guidelines from the American Academy of Sleep Medicine and American Academy of Pediatrics recommend PSG to confirm and characterize OSAS before adenotonsillectomy, 1,2,11 whereas the American Academy of Otolaryngology-Head and Neck Surgery recommends PSG for children with certain complex medical conditions or when there is discordance between tonsil size and reported severity of OSAS symptoms. 12 Less work has been done to define what adjunctive measures, in addition to PSG, may assist pediatricians, otolaryngologists, and families who are considering adenotonsillectomy to understand what adverse impact OSAS is having for the child and what the probability is that this adverse impact will be ameliorated by surgery. For example, few studies have examined whether baseline OSAS symptoms can predict postoperative changes in parentperceived behavior, sleepiness, and quality of life, outcomes that assume key importance to families, regardless of PSG results.…”
Section: What This Study Addsmentioning
confidence: 99%
“…The study patients underwent an overnight, in-laboratory attended PSG at baseline (PSG1), with follow-up 1 year after surgical intervention (PSG2 There is no international consensus regarding which AHI cutoff values to use when grading pediatric OSA, but according to clinical practice and several other authors, 14,15 an AHI ≤1 is considered normal, AHI >1 to <5 corresponds to mild OSA, AHI 5 to <10 moderate OSA, and AHI ≥10 severe OSA. In the current study, the upper limit of AHI 30 was chosen to avoid extreme values because AHI >30 is rare in children.…”
Section: Psgmentioning
confidence: 99%
“…Conference call 3 Review guideline appraisal report; remedy deficiencies [10][11] Prerelease peer review External review of draft guideline by representatives of target audience and practice settings 12 Public comment Guideline draft released for a period of public comment and review [13][14] Organizational board review and journal peer review Review and approval guideline by the board of directors of the sponsoring organization(s), with simultaneous submission to the journal for editorial peer review…”
Section: Medicine and Guidelinesmentioning
confidence: 99%
“…Many online services are now freely available for online collaboration and storage. Materials specific to the guideline that should be distributed include Agenda for the conference call Working group contact information grid with conflict of interest disclosures Summary grid of relevant systematic reviews and guidelines identified in the stage 1 literature search Relevant sections of the guideline development manual General materials that should be distributed include A copy of 1 or more recently published guidelines from the sponsoring organization [4][5][6][7][8][9][10][11] to serve as a model of how the finished product will look (all previously published AAO-HNSF guidelines are available at www.entnet.org/guidelines) Reporting checklist from the COGS 20 Articles by Norris and colleagues 30 and by Choudhry and coworkers 42 about conflict of interest disclosure and its relevance to guideline developers…”
Section: Predistribute Electronic Materialsmentioning
confidence: 99%